Atorvastatin mucoadhesive tablets in the management of recurrent aphthous stomatitis: a randomized clinical study - Tahereh Molania; Jafar Akbari; Amirhossein Babaei; Anahita Lotfizadeh; Mahmood Moosazadeh; Abbas Mesgarani; Anahita Baasl; Maede Salehi (BMC, 2023)
Abstract Background Aphthous stomatitis is one of the most common oral mucosal diseases. Due to the commonness of recurrent aphthous stomatitis and considering the anti-inflammatory, analgesic, and tissue regenerative properties of atorvastatin and the lack of a study on the effect of statins on minor recurrent aphthous stomatitis, this study investigates the effect of atorvastatin mucoadhesive tablets as a topical treatment on reduction of symptoms and duration of this disease. Methods This study is a randomized, double-blinded clinical trial. Patients were divided into two groups, atorvastatin and, placebo; each of the patients received three mucoadhesive tablets daily in the morning, noon, and night. Finally, the patients were examined on days 0 (baseline), 3, 5, and 7 to determine the diameter of the inflammatory halo. The VAS scale was used to evaluate pain intensity for up to 7 days after each meal. The data was entered into SPSS 24 software and analyzed. Results The halo diameter did not significantly differ between the two groups on baseline (P > 0.05). However, on the study's third, fifth, and seventh days, the difference between the two groups was remarkable, so in the atorvastatin group, the size of the lesions decreased in shorter healing time (P < 0.05). In addition, the patient's pain intensity (VAS) also showed a significant decrease in the atorvastatin group except on the first, second, and seventh days of the study (P < 0.05). Conclusion Atorvastatin mucoadhesive tablets effectively reduce the pain of patients with minor recurrent aphthous stomatitis and reduce the size and healing time of the lesions, so their application should be considered in treating minor recurrent aphthous stomatitis. The present study was approved by the Medical Ethics Committee of Mazandaran University of Medical Sciences with the ethics code IR.MAZUMS.REC.1400.8346. Also, this study received code IRCT20170430033722N4.